2014
DOI: 10.1128/mbio.00966-14
|View full text |Cite
|
Sign up to set email alerts
|

Within-Host Evolution of Pseudomonas aeruginosa Reveals Adaptation toward Iron Acquisition from Hemoglobin

Abstract: Pseudomonas aeruginosa airway infections are a major cause of mortality and morbidity of cystic fibrosis (CF) patients. In order to persist, P. aeruginosa depends on acquiring iron from its host, and multiple different iron acquisition systems may be active during infection. This includes the pyoverdine siderophore and the Pseudomonas heme utilization (phu) system. While the regulation and mechanisms of several iron-scavenging systems are well described, it is not clear whether such systems are targets for sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
165
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(182 citation statements)
references
References 35 publications
16
165
0
1
Order By: Relevance
“…A recent study demonstrates that in the CF lung, haem uptake is a critical source of iron for P. aeruginosa during chronic infection with more efficient utilization of haem by later compared with earlier isolates and consistent expression of the haemoxygenase HemO during prolonged infection (Nguyen et al, 2014). Further evidence of this adaptive response by P. aeruginosa is provided in a study by Marvig et al (2014) that demonstrated within-host evolution towards haem utilization, coupled with loss of pyoverdine production in three separate P. aeruginosa lineages (Marvig et al, 2014).…”
Section: Haem Uptake Systemsmentioning
confidence: 85%
“…A recent study demonstrates that in the CF lung, haem uptake is a critical source of iron for P. aeruginosa during chronic infection with more efficient utilization of haem by later compared with earlier isolates and consistent expression of the haemoxygenase HemO during prolonged infection (Nguyen et al, 2014). Further evidence of this adaptive response by P. aeruginosa is provided in a study by Marvig et al (2014) that demonstrated within-host evolution towards haem utilization, coupled with loss of pyoverdine production in three separate P. aeruginosa lineages (Marvig et al, 2014).…”
Section: Haem Uptake Systemsmentioning
confidence: 85%
“…Finally, further support for PhuR being the primary receptor for heme acquisition in P. aeruginosa comes from recent studies of clinical isolates where mutations within the phuR promoter, leading to increased PhuR expression, conferred a growth advantage in the presence of hemoglobin. Furthermore, this evolution within the host toward increased reliance on heme via up-regulation of PhuR coincides with loss of alternate iron-scavenging systems (39). Therefore, in acute infection the HasA-HasR system may play a more significant role in iron acquisition, however, on chronic infection bacteria adapt to utilize heme as an iron source through the high capacity Phu system.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast recent transcriptome analyses of P. aeruginosa longitudinal cystic fibrosis lung isolates suggested PhuR is the major heme receptor in clinical infection (39). Utilizing isotopic-labeling studies we have recently shown extracellular heme utilization is dependent on up-regulation of the phu system in clinical isolates (40).…”
mentioning
confidence: 91%
“…In 1973, DK2 acquired a mutation in the σ-factor fpvI gene, canceling up-regulation of receptor expression in the presence of pyoverdine ( Fig. 1) and also, lowering background receptor expression (18,27). This mutation is, however, followed by no fewer than 17 unique nonsynonymous fpvA mutations in nine independent lines across patients, suggesting that even limited background expression of fpvA is costly.…”
Section: Selection Targets Genes Involved In Both Pyoverdinementioning
confidence: 99%
“…Pyoverdine production may be an adaptive response to acquire a limited nutrient. It may be lost, therefore, in response to availability of other iron sources (18)(19)(20). Alternatively, production may be lost from the population even if iron is limiting as a result of…”
mentioning
confidence: 99%